Metabolomics study of treatment response to conbercept of patients with neovascular age-related macular degeneration and polypoidal choroidal vasculopathy - Shen, Yinchen; Wang, Hanying; Xu, Xiaoyin; Chen, Chong; Zhu, Shaopin; Cheng, Lu; Fang, Junwei; Liu, Kun; Xu, Xun (Frontiers in Pharmacology, 2022)
Graphical Abstract AMD, age-related macular degeneration; PCV, polypoidal choroidal vasculopathy; PLS-DA, partial least squares discriminant analysis; LPC, lysophosphatidylcholine; PC, phosphocholine; ROC, operating characteristic curve; AUC, area under the receiver operating characteristic curve; vWF, von Willebrand Factor. Note: The protein structure of vWF is downloaded from PDB (https://www.rcsb.org/).